High-Intensity Interval Training, but Not Whole-Body Cryostimulation, Affects Bone-Mechanosensing Markers and Induces the Expression of Differentiation Markers in Osteoblasts Cultured with Sera from Overweight-to-Obese Subjects - Gomarasca, Marta; Ziemann, Ewa; Sansoni, Veronica; Flis, Marta; Perego, Silvia; Jaworska, Joanna; Gerosa, Laura; Faraldi, Martina; Lombardi, Giovanni (Journal of personalized medicine, 2024)
Background/Objectives: Although there have been some clinical observations made, the mechanistic effects on bone metabolism of whole-body cryostimulation and high-intensity interval training (HIIT), either alone or in combination, are still debated. Here, we have investigated their effects on circulating osteo-immune and bone metabolic markers (osteopontin, osteocalcin, sclerostin, dikkopf-related protein 1, and fibroblast-growth factor 23) and their potential effects on osteoblast differentiation and function, in vitro, by treating SaOS-2 osteoblast-like cells with the sera obtained from the subjects who had undergone the different interventions or untreated control subjects. Methods: Sixty-seven inactive, overweight-to-obese participants (body mass index = 31.9 ± 5.0 kg·m−2, 42 ± 13 years old) were recruited and randomly assigned to one group: control (CTRL, n = 14), training (HIIT, 6 sessions, n = 13), WBC (CRYO, 10 sessions, n = 17) or training combined with WBC (CRYO-HIIT, n = 23). The interventions lasted 14 days. Results: While circulating markers analysis revealed more protective potential against resorption in HIIT than in WBC alone or combined, gene expression from in vitro analysis showed an induction of late bone metabolic markers in the HIIT group. Conclusions: These data suggest a potentially protective effect of HIIT in bone against resorption, while WBC maintains homeostasis by preventing any resorptive phenomena and limiting any anabolic activity even when stimulated by intensive exercise.